Desenvolvimento de aplicações web com a utilização dos frameworks CodeIgniter e Doctrine - Andrade, Fernando Francisco de (2011)
This is a study on the two Frameworks for developing WEB applications in PHP, CodeIgniter and Doctrine. Some characteristics of each as well as features and settings required to use. At the end is present a case study where the frameworks work together to perform the functionality of a WEB application.